Aktivitas Antimikobakteri serta Penentuan MIC–MBC Ekstrak Etanol Daun Clerodendrum minahassae terhadap Mycobacterium smegmatis - Palandi, Reky Royke; Lengkey , Yessie K.; Maarisit , Wilmar; Sumangando , Adolfina; Potalangi , Nerny A.; Karauwan , Ferdy A.; Tulandi , Selvana S.; Untu , Sonny D.; Pareta , Douglas N (Journal of Pharmaceutical and Sciences, 2026)
Tuberculosis remains a major global health challenge, particularly due to the increasing emergence of drug-resistant strains, highlighting the need for new antimycobacterial agents from natural sources. Clerodendrum minahassae, a medicinal plant traditionally used in North Sulawesi, has demonstrated antibacterial activity; however, its antimycobacterial potential has not been previously explored. This study aimed to evaluate the antimycobacterial activity of the ethanolic leaf extract of C. minahassae against Mycobacterium smegmatis as a surrogate model and to estimate its minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The extract was tested at concentrations of 5, 7.5, and 10 µg/disc using the disc diffusion method. Inhibition zone diameters increased in a concentration-dependent manner, ranging from 9.40 ± 0.52 mm to 10.60 ± 0.92 mm. Quantitative analysis using Bloomfield-based linear regression revealed a strong dose–response relationship (R² = 0.9926), from which MIC and MBC values of 0.63 µg/disc and 2.52 µg/disc were estimated, respectively. These findings indicate that the ethanolic extract of C. minahassae exhibits measurable inhibitory and bactericidal activity against M. smegmatis at relatively low concentrations. While this study represents an exploratory screening, the results support the potential of C. minahassae as a source of bioactive compounds with antimycobacterial relevance. Further investigations involving fractionation, compound identification, toxicity assessment, and validation against pathogenic Mycobacterium tuberculosis strains are warranted.